Photoinduced Ru-Yb energy transfer and sensitised near-IR luminescence in a coordination polymer containing co-crystallised [Ru(bipy)(CN)4]2- and Yb(III) units. - Miller, T; Jeffery, J; Ward, MD; Adams, H; Pope, S; Faulkner, S (2004)
Co-crystallisation of the anionic cyanometallate chromophore [Ru(bipy)(CN)4]2- with Yb(III) provides coordination polymers or oligomers containing Ru-CN-Yb bridges; in [K(H2O)4][Yb(H2O)6][Ru(bipy)(CN)4]2.5H2O Ru-->Yb energy-transfer (k > 5 x 10(6) s(-1)) results in partial quenching of the Ru-based luminescence and sensitised near-IR luminescence from the Yb(III) unit.